Write the quadratic equation in general form x-3)(x 2)=0

Question

Asked 1/23/2015 7:31:47 PM

Updated 1/24/2015 1:48:56 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/24/2015 1:48:06 AM]

rdsa77|Points 8703|

Question

Asked 1/23/2015 7:31:47 PM

Updated 1/24/2015 1:48:56 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/24/2015 1:48:06 AM]

Rating

3

The quadratic equation in general form (x-3)(x+2)=0 is x^2 - x - 6 = 0

(x - 3)(x + 2)

= x^2 - 3x + 2x - 6

= x^2 - x - 6

(x - 3)(x + 2)

= x^2 - 3x + 2x - 6

= x^2 - x - 6

Added 1/24/2015 1:48:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/24/2015 3:42:37 AM]

29,946,483

questions answered

There are no comments.